The Impact of Using Literature on Foreign Language Learning Development The Case of Third Year Secondary School (Biskra) - BENDAHMANE, Messaouda (University of Eloued جامعة الوادي, 2016)
Linguistics and literature are two interwoven domains though they seem different. They play a major role in one‘s (foreign) language learning process. In the 20th century, the relationship between linguistics and literature has changed and became more interesting to know that they can, together, enhance language learning/teaching. The development of the communicative approaches to language learning, the aim of language learning was to encourage the communicative competence in the foreign language, so that students would have the opportunity to express their ideas in the target language. Teaching literature can provide assistance in language learning as it makes teaching/ learning linguistic features easier and motivating. Using literary texts in teaching the assigned language forms is, then, of vital importance as it provides learners with authentic and cultural material for language learning and encourages their cognitive and communicative processes. In this paper, we shall shed light on two arguments for teaching literature in the foreign language class. 1. Literature helps in language acquisition through inferencing and narratives that suit students‘ cognitive development; 2. It gives access into the target culture and facilitates its potential contact with the learners‘ culture.
THE SECOND NATIONAL CONFERENCE ON LANGUAGE, MIND AND LEARNER'S COGNITIVE CAPACITIES March, 7th/8th 2016 University of Eloued
Keywords: language, literature, language acquisition, cognitive development, cultural awareness